Sensitivity Analysis of Live Sales Prices and Broiler Feed Costs - Cori Qamara; I Putu Gede Didik Widiarta (Journal of Tropical Animal Science and Technology, 2025)
The purpose of this study is to assess the sensitivity of broiler chicken producers' income to fluctuations in live chicken selling prices and feed costs in Samarinda City. The research was conducted using a simulation approach under several scenarios of price and cost adjustments, ranging from - 20% to + 20% of the base value. The findings show that changes in selling prices had a more linear influence on income, with a 10% increase in live chicken prices increasing revenue by about 13%. Feed expenses, on the other hand, have a more unequal effect on revenue, particularly as costs grow, resulting in significant profit margin reduction. These findings imply that farmers' income is extremely vulnerable to external market dynamics, both in terms of income and production costs. This study validates earlier research findings published in international journals, emphasizing the necessity of risk mitigation methods and cost efficiency as critical variables for the long-term viability of small- and medium-sized poultry farming operations. As a result, governmental measures are required to safeguard farmers from volatility in both input and product prices.